Geomorphologic analysis of the lower and middle section of the drainage basin of the Curri Leuvúriver, Neuquén - González Díaz, E.F. (2011)
The geomorphologic analysis of the study area led to distinguish some formations not considered in previous geological research, as well as to explain the characteristics of the present relief. Thirteen principal geomorphic units produced by different geomorphic processes are recognized. Their variety and incidence through the time are expressed in the glacial morphogenesis concentrated in the western part of the Cordillera del Viento, in the volcanic landscape that predominates in the northern and eastern sectors (calderas, volcanoes, lava flows), in the structural control that defines the morphology of the fluvial process in the central zone and a firstly recognized important landslide to the north of Tricao Malal. As a result of the methodology employed two geological units of different age in the western part of the Tromen-Waile volcanic field were distinguished, which were initially interpreted as a single formation. A limited but consistent structural analysis of the region is also included.